Teaching crowds: Learning and social media - Evelyn Frances Lewis (Flexible Learning Association of New Zealand, 2015)
In Teaching crowds: Learning and social media, Jon Dron and Terry Anderson examine the critical questions and emerging trends associated with the role of social software in the online learning environment. Drawing upon their extensive years of experience as online distance educators in the tertiary sector, Dron and Anderson suggest that the ability of social software to aggregate behaviour and choices is changing the nature of online learning. They contend that social software is set to become a significant feature of the online learning environment.